(untitled) (International Conference on Computers in Education, 2017)
We previously developed a research activity concierge (RAC) system, which is a platform to encompass general research activities, and applied gamification to this system to keep user motivation high. However, even with the RAC, non-research-savvy students have difficulty executing tasks. In this research, we introduced a mechanism to support task execution in research activities by implementing automatic task extraction into the RAC.